An acoustic method of determination of leakage coordinates in gas pipelines - BUTKUS, J.; JAKEVIČIUS, L.; TUMŠYS, O. (Archives of Acoustics, 1998)
The present paper describes an important leak-proofness of pipe-lines transporting gas, oil and other chemical liquids. It is revealed that one of the more perspective methods of detection of leakage coordinates of gas-lines is the acoustic correlation method. The employment of whistling acoustic noise propagating in the gas media filling the pipeline is proposed for the detection of leakage coordinates of gas pipelines. In accordance with the length of the pipe section under control and the desired precision of the determination of the leakage coordinates in the pipes, a method of choicing an optimal bandwidth of the filter and a sampling rate of received signals was developed. The results of experimental investigations are submitted. The method can be effectively used in checking the state of the pipe network as well as for solving the problems of management of the power economy objects and environmental protection.